Basic Concepts of Strategic Management in The Public Sector: A Theoretical Study and its Relevance in Governance in Indonesia - Yurisman Star; Aldi Pradana; Annisa Nur Khasanah; Ayu Yulian Anjani; David Sutrisno (Return : Study of Management, Economic and Bussines, 2025)
This paper discusses the basic concept of strategic management in the public sector and its relevance in the context of Indonesian governance. Using a descriptive-qualitative approach, the article outlines the main stages of strategic management—strategy formulation, implementation, and evaluation—and compares them with practices in the private sector. Furthermore, it explores the implications of applying this concept in public policy and government strategic planning, as well as the practical challenges and solutions encountered in the field. This study is expected to provide both conceptual and practical contributions to the development of more effective and accountable public governance.